2016
DOI: 10.1007/s11999-016-4776-5
|View full text |Cite
|
Sign up to set email alerts
|

Higher Pavlik Harness Treatment Failure Is Seen in Graf Type IV Ortolani-positive Hips in Males

Abstract: Background Patients with developmental dysplasia of the hip (DDH) whose hips are dislocated but reducible (Ortolani positive) are more likely to experience Pavlik harness treatment failure than are patients with dysplastic and reduced but dislocatable (Barlow positive) hips. However, data regarding factors associated with failure are limited and conflicting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 34 publications
3
45
3
Order By: Relevance
“…Male gender was considered a significant risk factor correlated with the failure of Pavlik’s method in two studies. 36 , 52 In one study, 93% of the male patients treated with the Pavlik harness at a mean age of seven weeks needed other treatment modalities. 52 Besides, the treatment duration was found to be somewhat longer in male than in female patients.…”
Section: Results Of Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Male gender was considered a significant risk factor correlated with the failure of Pavlik’s method in two studies. 36 , 52 In one study, 93% of the male patients treated with the Pavlik harness at a mean age of seven weeks needed other treatment modalities. 52 Besides, the treatment duration was found to be somewhat longer in male than in female patients.…”
Section: Results Of Treatmentmentioning
confidence: 99%
“… 10 , 24 , 27 , 34 , 35 , 37 39 , 42 , 45 , 46 , 48 Besides, the risk of failure in Graf type IV hips was found to be about four times higher than in Graf type III hips. 36 It is evident that the Graf type IV hip has the highest rate of failure among the hip types in Graf’s classification system. Besides, an alpha angle of less than 47° (sensitivity 47%, specificity 86%) was found to be the threshold value for the failure in Pavlik’s method.…”
Section: Results Of Treatmentmentioning
confidence: 99%
“…23 -25 Patient-related risk factors for failure of harness treatment included increased age at initiation of treatment (>7 weeks old), 25,26 multigravida birth, 27 the presence of a foot deformity, 27 and male sex. 24 The initial ultrasonographic severity of dysplasia in the Ortolani-positive hip is prognostic for the failure of Pavlik harness treatment, with more severely dislocated hips in which the labrum is interposed between the femoral head and acetabulum being associated with failure. 23 For those patients with an Ortolanipositive hip who fail to stabilize after initial Pavlik harness treatment, authors of recent literature suggest that a trial of a more rigid abduction hip orthosis, such as an Ilfeld orthosis (Fig 6)…”
Section: Figurementioning
confidence: 99%
“…Selecting these devices for the treatment of an unstable hip, especially a resting-dislocated (Ortolani) hip, may impose some risk on acetabular development and treatment outcome. Novais et al reported that Pavlik harness treatment failed in 27% of Ortolani-positive hips, compared with 8% of stable dysplastic hips and 5% of Barlow-positive hips [7]. High failure rates of the Pavlik harness in dislocated hips have been reported by other authors as well [8].…”
Section: Discussionmentioning
confidence: 85%